The Contextual Nature of Selected Divorce Determinants– Critical Analysis of the Literature - Andrzej Porębski; Ewa Ilczuk (Fabrica Societatis)
The main objective of this study is to demonstrate the complexity and contextual entanglements of factors affecting divorce probability. The paper examines the impact of worldview (including religi-osity), spousal education, presence of children in marriage, and economic situation. To achieve the aforementioned goal, acritical analysis of the selected literature was conducted and enriched with references to publicly available statistical data. The article is divided into four main sections, each dedicated to the impact of one of the four discussed factor groups on divorce risk. The argument is supported by critical references to the literature and offers possible mechanisms of influence. The analysis reveals that each examined factor can influence divorce probability, but the impact is high-ly susceptible to cultural change and varies over time, making generalizations to the global popula-tion difficult. The results of the study suggest aparticular need to consider and specify the cultural context in divorce probability research, along with the inclusion of abroader set of explanatory variables and their interactions.